The Relationship Between Negative Life Events and Mental Health in Chinese Vulnerable Children: A Meta-Analysis Based on the Dual-Factor Model of Mental Health - Yunrong Pu; Kuo Zhang; Xiaoliu Jiang (Behavioral Sciences, 2025)
While negative life events’(NLEs’) impact on vulnerable children’s mental health has been studied, the role of moderating variables remains unclear. Synthesizing the current evidence is critical to advancing understanding. Accordingly, this study conducted a meta-analysis utilizing a random-effects model across 77 studies, which collectively encompassed 119 effect sizes, to elucidate the connections between NLEs and mental health indicators among distressed children. The results revealed a significant positive correlation between NLEs and negative indicators of mental health (r = 0.42), reflecting strong and consistent associations. In contrast, NLEs were associated with a significant negative correlation with positive indicators of mental health (r = −0.25), reflecting weak and variable associations. Furthermore, the relationship between NLEs and the mental health of vulnerable children was found to be consistent across various age groups and subpopulations. These findings lay the groundwork for the development of targeted intervention strategies aimed at enhancing the mental well-being of vulnerable children.